Al-Tustar?'s Sufistic Comments on the Notion of Nafs - İnce, Eyüp (Fırat University, 2022)
The Qur??n was sent as a source of guidance to all humanity. To receive the best guidance, it is necessary to first read and appreciate the Qur??n and then to put it into practice. The Qur??n encompasses issues and notions that can readily be understood by all people in general. However, it is challenging to understand some topics and concepts. One of these challenging concepts is the nafs. Inspired by the Qur??n, the Sufi scholar al-Tustar? built his conception of Sufism on educating the nafs and dominating it. Therefore, al-Tustar?’s comments are critical in understanding and educating the nafs, which is home to many complicated feelings. This study examined the sufistic interpretations of the notion of nafs in al-Tustar?’s Tafs?r al-Qur??n al-?A??m. As a method, the study was primarily built upon the verses that al-Tustar? cites to support his thoughts about the nafs. Then, the sufistic interpretations he made about these verses were pinpointed, and the general framework of the study was constructed. While addressing the subject, the literal and technical meaning of the concept of nafs were mentioned and its explanations in the Qur??n and Sunnah were offered. Then, based on this information, al-Tustar?’s comments on the concept of nafs were discussed from a sufistic perspective. It was concluded that the notion of nafs in al-Tustar?'s interpretations has a great variety of meanings full of mysteries. Furthermore, it was clear from al-Tustar?'s comments that the nafs lowers a human to the state of asfal al-s?fil?n (the lowest of all levels of Hell), and when it is refined by endeavour and purification, it elevates him or her to the position of ?al? al-?illiyy?n (the highest levels of Heaven).

Kur’ân-ı Kerîm, tüm insanlığa bir hidayet kaynağı olarak gönderilmiştir. Hidayeti tam manasıyla elde etmek için öncelikle Kur’ân-ı Kerîm’i okuyup idrak edip daha sonrasında pratiğe dökmek gerekir. Kur’ân’ın içeriğinde genel olarak bütün insanların anlayabileceği konular ve kavramlar bulunmaktadır. Fakat bazı konuların ve kavramların anlaşılması güçtür. Anlaşılması güç olan kavramlardan biri de nefistir. Mutasavvıf Tüsterî, Kur’ân’dan aldığı ilhamla tasavvuf anlayışını, nefsi terbiye edip onu hâkimiyet altına alma üzerine kurmuştur. Bu açıdan Tüsterî’nin yorumları, komplike (karmaşık) duyguları barındıran nefsin anlaşılması ve terbiye edilmesi noktasında önem arz etmektedir. Bu çalışmada Tüsterî’nin Tefsîru’l-Kur’âni’l-Azîm isimli tefsirindeki nefis kavramına dâir tasavvufî yorumları incelenmiştir. Yöntem olarak öncelikle Tüsterî’nin nefisle alakalı düşüncelerine referans gösterdiği âyetler temel alınmıştır. Daha sonrasında Tüsterî’nin bu âyetlere getirmiş olduğu tasavvufî yorumlar tespit edilerek konunun genel çerçevesi belirlenmiştir. Konuyu ele alırken ise nefis kavramının lügat, ıstılah manası zikredilerek Kur’ân ve sünnetteki açıklamalarına yer verilmiştir. Daha sonra bu bilgiler çerçevesinde Tüsterî’nin nefis kavramına dâir yapmış olduğu yorumlar tasavvufî açıdan ele alınmıştır. Netice olarak Tüsterî’nin yorumlarında nefis kavramının sırlarla dolu bir anlam yelpazesine sahip olduğu görülmüştür. Ayrıca Tüsterî’nin yorumlarından, nefsin insanı esfeli sâfilîn (cehennemin en aşağısı) durumuna düşürdüğü gibi mücâhede ve tezkiye ile arındırıldığında âlâyı ıllıyyîn (cennetin en yüksek mertebeleri) konumuna yükselttiği tespit edilmiştir.
Tüsterî'nin Nefis Kavramına Dâir Tasavvufî Yorumları
Keywords: Religious Studies; Din Araştırmaları